Comparison of retinol binding protein 1 with cone specific G-protein as putative effector molecules in cryptochrome signalling - Chad Yee; Rabea Bartölke; Katharina Görtemaker; Jessica Schmidt; Bo Leberecht; Henrik Mouritsen; Karl-Wilhelm Koch (Scientific Reports)
Abstract Vision and magnetoreception in navigating songbirds are strongly connected as recent findings link a light dependent radical-pair mechanism in cryptochrome proteins to signalling pathways in cone photoreceptor cells. A previous yeast-two-hybrid screening approach identified six putative candidate proteins showing binding to cryptochrome type 4a. So far, only the interaction of the cone specific G-protein transducin α-subunit was investigated in more detail. In the present study, we compare the binding features of the G-protein α-subunit with those of another candidate from the yeast-two-hybrid screen, cellular retinol binding protein. Purified recombinant European robin retinol binding protein bound retinol with high affinity, displaying an EC50 of less than 5 nM, thereby demonstrating its functional state. We applied surface plasmon resonance and a Förster resonance transfer analysis to test for interactions between retinol binding protein and cryptochrome 4a. In the absence of retinol, we observed no robust binding events, which contrasts the strong interaction we observed between cryptochrome 4a and the G-protein α-subunit. We conclude that retinol binding protein is unlikely to be involved in the primary magnetosensory signalling cascade.